Borders, Roads and the Relocation of Economic Activity Due to Extreme Weather - Jasmin Katrin Gröschl; Thomas Steinwachs (Center for Economic Studies and ifo Institute (CESifo), 2020)
Extreme weather may give rise to the relocation of economic activity towards nearby locations. But how are the economic effects of weather events transmitted between locations? And, which role does the interconnection of small economic units play? This paper takes a granular approach to identify the role of connectivity on economic activity due to severe weather. We combine a 0.5°0.5° grid-cell level dataset on economic activity and weather events with global geographic information on national borders and road networks. We first explore how a potential disruption of connectivity through an international border affects local spillovers in case of a weather shock. Second, we use road infrastructure as a proxy for overall connectivity to explore how this affects the diversion of economic activity across local economic units. Results suggest that international borders limit economic relocation due to extreme weather to domestic neighboring cells. The existence of major road infrastructure between locations is key to the relocation of economic activity due to a weather event. Without a transport network, spillovers between local economic units do, on average, not exist or are at least very limited and costly to implement.
Keywords: F15; O18; Q54; R11; 330; light emission; weather; connectivity; border effect; road network